The scientometric evaluation of the institutional research: The Marmara Universities-Part 3 - Konur, Özcan (SILA SCIENCE, 2013)
The scientometric analysis of the research has become one of the most used methods to assess the research performance of the scholars, departments, faculties, universities, countries, and journals in recent years. However, there has not been an extensive scientometric evaluation of the institutional research carried out by the universities in the Marmara Region of Turkey, to examine the development of the research over time. Hence, the purpose of this study was to carry out a scientometric evaluation of the research performed by these universities using three indices in a series of four papers. In the third part of these serial papers, it was found that the placement of incorrect names for the university name in the affiliation section of the abstract pages of the papers was a serious problem especially for the institutions with more than two words in their names resulting in the lack of visibility in the institutional rankings. The preferred name format for the name of the institutions was "x univ" rather than "univ x". There were 57,860 articles and reviews published by these universities and 94.6% of these papers were indexed by the SCIE as they were related to Natural and Applied Sciences. Only 7.5% and 1.1% of these papers were indexed by SSCI and A&HCI, respectively as they were concerned with Social Sciences and Arts & Humanities. There were strong Social Sciences and Arts and Humanities deficits in the research output of Marmara Universities. These results were in line with the results relating to the research productivity of Turkish Universities at a national scale. The most prolific author was "Sen Z" of the Department of the Civil Engineering, Istanbul Technical University and the most prolific authors were from Istanbul Technical University (5), Koc University (1), Kadir Has University (1), Istanbul University (2), and Gebze Institute of Advanced Technology (1). The most prolific authors were from the Natural Sciences departments, the Engineering departments and Health Sciences departments. It is thus notable that there were not any most prolific authors from Social Sciences as well as Humanities & Arts. It was found that the top most prolific institution in terms of the number of publications was Istanbul University and the SSCI and A&HCI-related relative subject dominance was pronounced for the Yeditepe University, Marmara University, and Sakarya University. The top university in terms of the H-index was Istanbul University with H-index of more than 100, closely followed by the Bogazici University, Istanbul Technical University, Marmara University, and Koc University with H-index of 83, 78, 60, and 55, respectively. The results found in the third part suggest that there was a close structure-research performance relationships for these universities hinting the strong effect of the formal and informal rules adapted by these universities on their respective research productivity following North's new institutional theoretical framework
Keywords: AandHCI; Humanities; SSCI; SCIE; Web of Knowledge; Turkey; Incentive structures; Marmara Universities; Research evaluation; Research productivity; Scientometrics; Social Sciences